2013
DOI: 10.1080/03632415.2013.777664
|View full text |Cite
|
Sign up to set email alerts
|

Status of White Sturgeon in the Lower Fraser River, British Columbia

Abstract: Sturgeon (Acipenseridae) stocks worldwide are generally in decline, with many populations close to extirpation. One prominent species, the White Sturgeon (Acipenser transmontanus) with spawning populations distributed throughout three large, western North American watersheds (the Sacramento, Columbia, and Fraser rivers), has experienced population declines in the past decade. In 2003, the Committee on the Status of Endangered Wildlife in Canada designated all six populations of White Sturgeon in Canada “endang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 7 publications
2
35
0
Order By: Relevance
“…In Canada, White Sturgeon are of cultural and economic importance. The species has been important to aboriginals for generations (Nelson et al 2013b), actively targeted by anglers (Inglis and Rosenau 1994), and at one time was commercially exploited (Semakula and Larkin 1968), although overfishing caused the fishery to collapse at the turn of the last century (Echols and FRAP 1995;Ptolemy and Vennesland 2003). White Sturgeon are long-lived, latematuring fish (Semakula and Larkin 1968); thus it is not surprising that populations have been slow to recover from the great declines caused by overfishing.…”
mentioning
confidence: 99%
“…In Canada, White Sturgeon are of cultural and economic importance. The species has been important to aboriginals for generations (Nelson et al 2013b), actively targeted by anglers (Inglis and Rosenau 1994), and at one time was commercially exploited (Semakula and Larkin 1968), although overfishing caused the fishery to collapse at the turn of the last century (Echols and FRAP 1995;Ptolemy and Vennesland 2003). White Sturgeon are long-lived, latematuring fish (Semakula and Larkin 1968); thus it is not surprising that populations have been slow to recover from the great declines caused by overfishing.…”
mentioning
confidence: 99%
“…The use of uniquely identifiable tags can provide comparative growth and condition information for long-term studies with adequate sample sizes [68]. Length data (i.e., fork length) collected during initial tag release events and again during subsequent recaptures can be used to calculate daily growth rates for individual fish (based on the number of days at large between the release and subsequent recapture events).…”
Section: Research Techniquesmentioning
confidence: 99%
“…Length data (i.e., fork length) collected during initial tag release events and again during subsequent recaptures can be used to calculate daily growth rates for individual fish (based on the number of days at large between the release and subsequent recapture events). Daily growth can be expanded to provide estimates of annual growth, which in turn can be pooled and averaged for size/age groups of fish; these comparative data can provide insights regarding changes in overall population growth rates and condition over time [68].…”
Section: Research Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples from other areas in Florida have shown that the exclusion or alienation of stakeholders in resource management can lead to stakeholder frustration and a lack of acceptance and compliance with management decisions (Suman et al 1999). The creation of citizen science programs similar to this study has the potential to better integrate anglers into restoration and conservation efforts (Nelson et al 2013), with clear benefits in the form of public support and improved research results.…”
Section: Citizen Sciencementioning
confidence: 99%